Necessity of The Abhidhamma for The Interpretation of Early Buddhist Discourses - Santacitto Sentot (Jounal Nyanadassana, 2022)
This paper presents an overview about the necessity of the Abhidhamma for interpreting several main teachings found in the early Buddhist discourses. The study is based on the Tipiṭaka and some other information taken from exegetical literatures (Aṭṭhakathā). Several important points found in the early Buddhist discourses are critically analyzed in the light of the Abhidhamma. It is found that certain points referring the two kinds of truths which have not been clearly distinguished in the early discourses, are made clear in the Abhidhamma by introducing the two kinds truths, namely sammutisacca and paramatthasacca. Furthermore, some controversial matters such as the doctrine of puggala promulgated by some Buddhist schools, and the wrong views of eternalists and nihilists which are often stated in the early Buddhist discourses but yet not so much discussed, are successfully refuted in the Abhidhamma. Thus, the present study has highlighted the importance of Abhidhamma in giving a better explanation regarding some important and controversial points found in the early discourses.